Smart Tax Governance: Empirical Evidence for an Integrated Accounting Legal Reform Model in Egypt - Lotfy, Amin ElSayed Ahmed (Santoso Academy Network, 2025)
This study proposes an original and integrated accounting legal reform model to proactively prevent and resolve tax disputes in Egypt, a framework not previously developed or empirically tested in the national context. It addresses persistent systemic challenges, including ambiguous tax regulations, inconsistent accounting documentation, prolonged dispute resolution processes, and low stakeholder trust. Using a mixed-methods approach, data were collected from surveys of 300 stakeholders tax auditors, certified public accountants, legal experts, and corporate taxpayers supplemented by semi-structured interviews and international benchmarking with advanced tax jurisdictions. Intelligent simulation tools were employed to evaluate alternative legal accounting structures and predict dispute trajectories. The findings show that tax disputes decline significantly when accounting transparency, legal codification, and digital governance are integrated within a unified framework. The proposed model demonstrates strong predictive capacity for identifying high-risk disputes and enabling early intervention. Stakeholder engagement further improves the feasibility and acceptance of the reforms. Policy implications indicate that Egypt’s litigation-oriented tax dispute system can transition toward proactive governance through coordinated legal reforms, standardized accounting practices, and digital intelligence, aligning national tax governance with OECD standards and Egypt Vision 2030.